Microbiological and molecular epidemiological analyses of community-associated methicillin-resistant Staphylococcus aureus at a tertiary care hospital in Japan. Issue 10 (October 2015) - Inomata, Shinya; Yano, Hisakazu; Tokuda, Koichi; Kanamori, Hajime; Endo, Shiro; Ishizawa, Chiyuki; Ogawa, Miho; Ichimura, Sadahiro; Shimojima, Masahiro; Kakuta, Risako; Ozawa, Daiki; Aoyagi, Tetsuji; et al.
Abstract Molecular characterization of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) is generally conducted referred to staphylococcal cassette chromosome mec (SCCmec) type IV or V. CA-MRSA is now a cause of concern since such strains have been isolated not only from individuals in a community but also from patients in healthcare settings. The aim of this study was to analyze microbiological and molecular epidemiological features of CA-MRSA strains at a Japanese tertiary care hospital using PCR based-open reading frame typing (POT). This technique allows for molecular classification into CA-MRSA (POT-CA) and hospital-associated (HA-) MRSA (POT-HA) with clonal discrimination. Clinical MRSA isolates obtained from consecutive patients between October 1, 2012 and September 30, 2013 at the hospital were analyzed in combination with the clinical definition for CA-MRSA by the Centers for Disease Control and Prevention and POT. Of 219 isolates (76 clonal groups), 64 (29.3%) were clinical-HA/POT-CA isolates (22 clonal groups). Some clones of them accumulated in this hospital and might be involved in nosocomial transmission. Virulent factors of the isolates were analyzed, and only one (1.6%) Panton-Valentine leukocidin gene positive isolate but no arginine catabolic mobile element genes positive isolate were found in clinical-HA/POT-CA. Additionally, clinical-HA/POT-CA isolates showed higher antimicrobial susceptibility than clinical-HA/POT-HA, especially to minocycline, doxycycline, and amikacin. The most frequent genotype of molecular CA-MRSA was multi-locus sequence type 5-SCCmecIV, previously not detected in Japan. Although CA-MRSA at this hospital showed low virulence and higher antimicrobial susceptibility, the risk of nosocomial infection from them should be recognized, requiring stricter infection control measures.